Enhancing crop yield and conserving soil moisture through mulching practices in dryland agriculture - Demo, Addis Hailu; Asefa Bogale, Girma (Frontiers in Agronomy, 2024)
Dryland agriculture requires the efficient utilization of water resources and the implementation of water-conserving technologies. Mulching is a water conservation practice used in arid land areas to preserve soil moisture, control temperature, and minimize soil evaporation rates. Organic mulching minimizes soil deterioration, enhances organic matter, and boosts the soil’s ability to retain water. Mulching can help keep moisture in the root zone, allowing plants to receive water for extended periods. Mulching with composted yard waste led to higher soil nutrient levels, including phosphorus (P), potassium (K), calcium (Ca), and organic matter when compared to uncovered soil. Under plastic mulch, soluble nutrients such as nitrate (NO3−), ammonium (NH4+), calcium (Ca2+), magnesium (Mg2+), potassium (K+), and fulvic acid are released as organic matter decomposes, enhancing the soil’s nutrient availability. Mulching has several advantages for dryland agriculture, such as reducing soil water loss, soil erosion, weed growth, water droplet kinetic energy, and competition for nutrients and water with nearby fields. This review article aimed to demonstrate the effectiveness of ground mulching in water conservation. This is particularly important in arid regions where agricultural sustainability is at risk due to drought, heat stress, and the inefficient use of limited water resources during the cropping season. Ground mulching is essential for minimizing surface evaporation and hence decreasing water loss. This review research thoroughly examines the advantages of organic and synthetic mulches in crop production, as well as their use in the preservation of soil and water resources.